Корпорація – організаційно-правова форма корпоративних відносин - Борисова, В. І. (Право, 2015)
Стаття присвячена окремим проблемам корпорації як однієї з найбільш динамічних і водночас усталених організаційно-правових форм, в якій проявляються корпоративні відносини. // The article is devoted to separate problems of the corporation as one of the most dynamic and at the same time established organizational and legal forms, in which corporate relations are manifested.
Keywords: корпорація; корпоративні відносини; афілійовані особи; організаційно-правова форма; орган юридичної особи; юридична особа; corporation; corporate relations; affiliated persons; organizational and legal form; authority of a legal entity; legal entity